Cooperaţia în România – actor al economiei sociale - Petrescu, Claudia (Calitatea Vieții, 2011)
In the last years the policy debates around the social economy have increased in Romania. Social economy represents a solution for social inclusion issues. Cooperatives represent border entities based on two components – economic and social. They were marginalized by the economic approaches due to the fact that the main microeconomic principles – the presence of only self-interested individuals and profit-maximisation – has limited applicability to the case of cooperatives. This article aims to present the cooperatives sector in Romania and their role in social economy sector.